Problems and prospects of development of car building enterprises of ukraine (Transport systems and technologies, 2020)
The article studies the current state of the car - building industry in Ukraine, discusses main problems and development prospects of railcar industry and preconditions of their occurrence. The problems that constrain the development of the car - building complex of Ukraine are formulated. The main ways of solving modern problems and proposals for improving the work of car - building enterprises of Ukraine are given. The perspective directions of the development of the national car - building industry have been identified.The need to make specific decisions on the large-scale development of railroad construction enterprises, the importance of strengthening partnerships with foreign railroad enterprises, combined efforts of domestic transport companies to create new innovative products, development of railway infrastructure, international transport corridors and many transport aspects.Also considered is the direction of movement of the world car-building enterprises, and the role of rail transportation in the life of an economically developed country.
Keywords: car-building enterprises, problems, prospects, development